A Comprehensive Ethno-Phyto-Pharmacological Review on Novel Indian Medicinal Plants Used In Polyherbal Formulations - Pulak Majumder; Paridhavi M (International Journal of Phytomedicine, 2013)
Almost 15% out of the 20,000 medicinal plants in Indian sub continent has a tremendous potential and advantage in the emerging field of herbal medicines. Medicinal plants are the main sources of chemical substances with potential therapeutic effects. A lot of compounds were characterized from plants which are now using in the treatment of many diseases. Since ancient times, plants have been an exemplary source of medicine. Ayurveda and other Indian literature mentioned the use of plants in treatment of various human ailments. Medical plants play an important role in the management of different clinical problems especially in developing countries where resources are meager The present paper reviews the literature on recent ethno medicinal uses with pharmacological screeing of every plant part of different five medicinal plants, i.e Cassia Auriculata Linn, Cinnamomum tamala, Ficus benghalensis, Trichosynthes dioica and Mangifera indica and their phytochemical properties used for the treatment of various ailments in human civilization as well as used in folk medicine as a remedy. The name and parts of the plant studied, the spectrum of activity, and methods used are discussed in this review paper.